Method Determining the Contents of the Contract - Agus Yudha Hernoko; Ghansham Anand; Fiska Silvia Raden Roro (Hasanuddin Law Review, 2017)
The contents of the contract are primarily determined by what the real mutually agreed upon by the parties. By interpreting some certain statements, in this case to determine its meaning, to be clear based on what the parties committed themselves. Why is the interpretation required? In facts, on the many cases provided a valuable lesson, how many commercial disputes arise when the performance of the contract. The dispute begins when the parties have a different understanding of the statement that they use in the contract. Indeed, businesses are very familiar with the business processes that they do, but at the time of the business process are set forth in the contract language and designed by those who do not understand the legal aspects of the contract, the contract can be ascertained open possibility for disputes. The power of contract binding (the contents of the agreement) toward to the characteristic and the wide spectrum of the rights and obligations contractually, basically a contract represents the power of performance among others in order implementing the rights and obligations of the parties. As an instrument to understand the contract, the method of determining the content of the contract (e.g., through interpretation, autonomous and heteronomous factors), further can be used to assess the reciprocation of rights and obligations in a meaningful and proportional contractual relationship.